Biological Activity of the Coordinating Compound of Qinazolin-4-One with Nickel-(II) Nitrate Hexahydrate - Obloyorov Aziz Ulfat o’g’li; Nasimov Hasan Murodovich; Aronbaev Sergey Dmitrievich; Saitkulov Foziljon Ergashevich (Zien Journals, 2023)
We performed the following processes in the study of the biochemical effects of the coordination compound formed with nickel (II)-nitrate and quinazolin-4-one on the "amber" variety of the Phaseolus aureus plant.
Keywords: coordination compound; quinazolin-4-one; nickel; anthranilic acid